Human recreation influences activity of a large carnivore in an urban landscape - Ellen C. Bolas; Adam D. Pingatore; Maya Mathur; Daniel T. Blumstein; Jeff A. Sikich; Justine A. Smith; John F. Benson; Seth P.D. Riley; Rachel V. Blakey (Biological Conservation, 2025)

A Functional Response in Resource Selection Links Multiscale Responses of a Large Carnivore to Human Mortality Risk - Kyle D. Dougherty; Justin A. Dellinger; Bogdan Cristescu; Daniel J. Gammons; David K. Garcelon; J. Mark Higley; Quinton E. Martins; Seth P. D. Riley; Jeff A. Sikich; Thomas R. Stephenson; T. Winston Vickers; Greta M. Wengert; et al. (Ecology Letters, 2025)
Theory suggests that animals make hierarchical, multiscale resource selection decisions to address the hierarchy of factors limiting their fitness. Ecologists have developed tools to link population‐level resource selection across scales; yet, theoretical expectations about the relationship between coarse‐ and fine‐scale selection decisions at the individual level remain elusive despite their importance to fitness. With GPS‐telemetry data collected across California, USA, we evaluated resource selection of mountain lions ( Puma concolor ; n = 244) relative to spatial variation in human‐caused mortality risk. With hierarchical resource selection, coarse‐scale selection determines availability at finer scales. This simple relationship allowed us to demonstrate that functional responses in resource selection explicitly link individual‐level resource selection decisions across scales. We show that individuals proactively avoiding risk when selecting home ranges are freed to relax this avoidance when making decisions within home ranges. However, individuals also exhibit reactive avoidance of risk at the finest scales along movement paths.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Balancing conflict and opportunity - spatial planning of shellfish and macroalgae culture systems in a heavily trafficked maritime port - Lisa C. Wickliffe; Jonathan A. Jossart; Seth J. Theuerkauf; Brandon M. Jensen; John B. King; Trent Henry; Paula C. Sylvia; James A. Morris; Kenneth L. Riley (Frontiers in Marine Science, 2024)
Ocean-based industries like shipping, aquaculture, and wind energy are growing at an unprecedented rate resulting in challenges related to siting and environmental management. As marine aquaculture and other ocean-based industries continue to expand, robust marine spatial planning analyses that reconcile existing ocean uses and integrate pertinent environmental and planning data are critical for identifying compatible locations. In this study, a series of geospatial analyses were used for aquaculture siting within and around a heavily trafficked and highly utilized maritime port in the San Diego Bay area of California, USA. Using a centralized geodatabase representing key aquaculture planning spatial datasets, recommendations for specific areas for aquaculture were developed based on appropriate environmental conditions for candidate shellfish and algae aquaculture species culture systems. Areas that were known constraints were first identified to determine potentially usable areas for shellfish and macroalgae (i.e., seaweed) aquaculture using an exclusion analysis, a type of multi-criteria decision analysis, to eliminate all areas without compatibility. Within the remaining usable area, we further considered shellfish and macroalgae culture system-specific factors within a ‘culture systems analysis’ to determine where different culture systems have potential for success. This analysis provides a foundation of coastal intelligence for guiding the aquaculture industry and natural resource managers towards appropriate siting decisions. This study can serve as a replicable example of aquaculture spatial planning approaches for siting sustainable aquaculture and other blue economy industries.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Birds of feather flock together: A longitudinal study of a social media outreach effort - Sarah Cavanah; Seth Owens; Kaylan Kemink; Collin Riley; Soojung Kim; Joonghwa Lee; Susan Ellis-Felege (Biological Conservation, 2023)

A circovirus and cycloviruses identified in feces of bobcats (Lynx rufus) in California - Gabriella M. Cerna; Laurel E. K. Serieys; Seth P. D. Riley; Cécile Richet; Simona Kraberger; Arvind Varsani (Archives of Virology, 2023)

Novel polyomaviruses identified in fecal samples from four carnivore species - Simona Kraberger; Laurel E. K. Serieys; Seth P. D. Riley; Kara Schmidlin; Eric S. Newkirk; John R. Squires; Christopher B. Buck; Arvind Varsani (Archives of Virology, 2023)

Lessons for conservation from beneath the pavement - Alexis M. Mychajliw; Elizabeth R. Ellwood; Peter S. Alagona; R. Scott Anderson; Mairin A. Balisi; Eric Biber; Justin L. Brown; Jessie George; Austin J. W. Hendy; Lila Higgins; Courtney A. Hofman; Ashley Leger; et al. (Conservation Biology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Urbanization reduces genetic connectivity in bobcats ( Lynx rufus ) at both intra– and interpopulation spatial scales - Christopher P. Kozakiewicz; Christopher P. Burridge; W. Chris Funk; Patricia E. Salerno; Daryl R. Trumbo; Roderick B. Gagne; Erin E. Boydston; Robert N. Fisher; Lisa M. Lyren; Megan K. Jennings; Seth P. D. Riley; Laurel E. K. Serieys; et al. (Molecular Ecology, 2019)
Urbanization is a major factor driving habitat fragmentation and connectivity loss in wildlife. However, the impacts of urbanization on connectivity can vary among species and even populations due to differences in local landscape characteristics, and our ability to detect these relationships may depend on the spatial scale at which they are measured. Bobcats ( Lynx rufus ) are relatively sensitive to urbanization and the status of bobcat populations is an important indicator of connectivity in urban coastal southern California. We genotyped 271 bobcats at 13,520 SNP loci to conduct a replicated landscape resistance analysis in five genetically distinct populations. We tested urban and natural factors potentially influencing individual connectivity in each population separately, as well as study–wide. Overall, landscape genomic effects were most frequently detected at the study–wide spatial scale, with urban land cover (measured as impervious surface) having negative effects and topographic roughness having positive effects on gene flow. The negative effect of urban land cover on connectivity was also evident when populations were analyzed separately despite varying substantially in spatial area and the proportion of urban development, confirming a pervasive impact of urbanization largely independent of spatial scale. The effect of urban development was strongest in one population where stream habitat had been lost to development, suggesting that riparian corridors may help mitigate reduced connectivity in urbanizing areas. Our results demonstrate the importance of replicating landscape genetic analyses across populations and considering how landscape genetic effects may vary with spatial scale and local landscape structure.

Novel smacoviruses identified in the faeces of two wild felids: North American bobcat and African lion - Simona Kraberger; Laurel Serieys; Nicolas Fountain-Jones; Craig Packer; Seth Riley; Arvind Varsani (Archives of Virology, 2019)

Genetic source–sink dynamics among naturally structured and anthropogenically fragmented puma populations - Kyle D. Gustafson; Roderick B. Gagne; T. Winston Vickers; Seth P. D. Riley; Christopher C. Wilmers; Vernon C. Bleich; Becky M. Pierce; Marc Kenyon; Tracy L. Drazenovich; Jeff A. Sikich; Walter M. Boyce; Holly B. Ernest (Conservation Genetics, 2019)

Genome‐wide expression reveals multiple systemic effects associated with detection of anticoagulant poisons in bobcats ( Lynx rufus ) - Devaughn Fraser; Alice Mouton; Laurel E. K. Serieys; Steve Cole; Scott Carver; Sue Vandewoude; Michael Lappin; Seth P.D. Riley; Robert Wayne (Molecular Ecology, 2018)
Anticoagulant rodenticides ( AR s) are indiscriminate toxicants that threaten nontarget predatory and scavenger species through secondary poisoning. Accumulating evidence suggests that AR exposure may have disruptive sublethal consequences on individuals that can affect fitness. We evaluated AR ‐related effects on genome‐wide expression patterns in a population of bobcats in southern California. We identify differential expression of genes involved in xenobiotic metabolism, endoplasmic reticulum stress response, epithelial integrity and both adaptive and innate immune function. Further, we find that differential expression of immune‐related genes may be attributable to AR ‐related effects on leucocyte differentiation. Collectively, our results provide an unprecedented understanding of the sublethal effects of AR exposure on a wild carnivore. These findings highlight potential detrimental effects of AR s on a wide variety of species worldwide that may consume poisoned rodents and indicate the need to investigate gene expression effects of other toxicants added to natural environments by humans.

Determining the drivers of population structure in a highly urbanized landscape to inform conservation planning - Henri A. Thomassen; Ryan J. Harrigan; Kathleen Semple Delaney; Seth P. D. Riley; Laurel E. K. Serieys; Katherine Pease; Robert K. Wayne; Thomas B. Smith (Conservation Biology, 2018)
Understanding the environmental contributors to population structure is of paramount importance for conservation in urbanized environments. We used spatially explicit models to determine genetic population structure under current and future environmental conditions across a highly fragmented, human‐dominated environment in Southern California to assess the effects of natural ecological variation and urbanization. We focused on 7 common species with diverse habitat requirements, home‐range sizes, and dispersal abilities. We quantified the relative roles of potential barriers, including natural environmental characteristics and an anthropogenic barrier created by a major highway, in shaping genetic variation. The ability to predict genetic variation in our models differed among species: 11–81% of intraspecific genetic variation was explained by environmental variables. Although an anthropogenically induced barrier (a major highway) severely restricted gene flow and movement at broad scales for some species, genetic variation seemed to be primarily driven by natural environmental heterogeneity at a local level. Our results show how assessing environmentally associated variation for multiple species under current and future climate conditions can help identify priority regions for maximizing population persistence under environmental change in urbanized regions.

FAST‐TRACK: A southern California freeway is a physical and social barrier to gene flow in carnivores - SETH P. D. RILEY; JOHN P. POLLINGER; RAYMOND M. SAUVAJOT; ERIC C. YORK; CASSITY BROMLEY; TODD K. FULLER; ROBERT K. WAYNE (Molecular Ecology, 2006)
Roads present formidable barriers to dispersal. We examine movements of two highly mobile carnivores across the Ventura Freeway near Los Angeles, one of the busiest highways in the United States. The two species, bobcats and coyotes, can disappear from habitats isolated and fragmented by roads, and their ability to disperse across the Ventura Freeway tests the limits of vertebrates to overcome anthropogenic obstacles. We combine radio‐telemetry data and genetically based assignments to identify individuals that have crossed the freeway. Although the freeway is a significant barrier to dispersal, we find that carnivores can cross the freeway and that 5–32% of sampled carnivores crossed over a 7‐year period. However, despite moderate levels of migration, populations on either side of the freeway are genetically differentiated, and coalescent modelling shows their genetic isolation is consistent with a migration fraction less than 0.5% per generation. These results imply that individuals that cross the freeway rarely reproduce. Highways and development impose artificial home range boundaries on territorial and reproductive individuals and hence decrease genetically effective migration. Further, territory pile‐up at freeway boundaries may decrease reproductive opportunities for dispersing individuals that do manage to cross. Consequently, freeways are filters favouring dispersing individuals that add to the migration rate but little to gene flow. Our results demonstrate that freeways can restrict gene flow even in wide‐ranging species and suggest that for territorial animals, migration levels across anthropogenic barriers need to be an order of magnitude larger than commonly assumed to counteract genetic differentiation.

Effects of Urbanization on the Distribution and Abundance of Amphibians and Invasive Species in Southern California Streams - SETH P. D. RILEY; GARY T. BUSTEED; LEE B. KATS; THOMAS L. VANDERGON; LENA F. S. LEE; ROSI G. DAGIT; JACOB L. KERBY; ROBERT N. FISHER; RAYMOND M. SAUVAJOT (Conservation Biology, 2005)
Urbanization negatively affects natural ecosystems in many ways, and aquatic systems in particular. Urbanization is also cited as one of the potential contributors to recent dramatic declines in amphibian populations. From 2000 to 2002 we determined the distribution and abundance of native amphibians and exotic predators and characterized stream habitat and invertebrate communities in 35 streams in an urbanized landscape north of Los Angeles (U.S.A.). We measured watershed development as the percentage of area within each watershed occupied by urban land uses. Streams in more developed watersheds often had exotic crayfish (Procambarus clarkii) and fish, and had fewer native species such as California newts (Taricha torosa) and California treefrogs (Hyla cadaverina). These effects seemed particularly evident above 8% development, a result coincident with other urban stream studies that show negative impacts beginning at 10–15% urbanization. For Pacific treefrogs (H. regilla), the most widespread native amphibian, abundance was lower in the presence of exotic crayfish, although direct urbanization effects were not found. Benthic macroinvertebrate communities were also less diverse in urban streams, especially for sensitive species. Faunal community changes in urban streams may be related to changes in physical stream habitat, such as fewer pool and more run habitats and increased water depth and flow, leading to more permanent streams. Variation in stream permanence was particularly evident in 2002, a dry year when many natural streams were dry but urban streams were relatively unchanged. Urbanization has significantly altered stream habitat in this region and may enhance invasion by exotic species and negatively affect diversity and abundance of native amphibians.

Effects of Urbanization and Habitat Fragmentation on Bobcats and Coyotes in Southern California - Seth P. D. Riley; Raymond M. Sauvajot; Todd K. Fuller; Eric C. York; Denise A. Kamradt; Cassity Bromley; Robert K. Wayne (Conservation Biology, 2003)
Urbanization and habitat fragmentation are major threats to wildlife populations, especially mammalian carnivores. We studied the ecology and behavior of bobcats ( Lynx rufus ) and coyotes ( Canis latrans ) relative to development in a fragmented landscape in southern California from 1996 to 2000. We captured and radiocollared 50 bobcats and 86 coyotes, determined home ranges for 35 bobcats and 40 coyotes, and measured their exposure to development ( “urban association” ) as the percentage of each home range composed of developed or modified areas. Both species occupied predominantly natural home ranges. Adult female bobcats had low levels of urban association, significantly lower than coyotes, adult male bobcats, and young female bobcats. Home‐range size was positively correlated with urban association for coyotes and adult male and young female bobcats, suggesting that human‐dominated areas were less suitable than natural areas in some important way. Animals more associated with non‐natural areas had higher levels of night activity, and both bobcats and coyotes were more likely to be in developed areas at night than during the day. Survival rates were relatively high and were not related to urban association, at least for animals>6–9 months of age. Mortality rates from human‐related causes such as vehicle collisions and incidental poisoning were also independent of urban association. In this region, even the few animals that had almost no human development within their home range were vulnerable to human‐related mortality. Carnivore conservation in urban landscapes must account for these mortality sources that influence the entire landscape, including reserves. For bobcats, preserving open space of sufficient quantity and quality for adult females is necessary for population viability. Educating local residents about carnivores is also critical for conserving populations in urban areas.